Scuba Diving Activates Vascular Antioxidant System - Sureda, A.; Batle, J. M.; Ferrer, M. D.; Mestre-Alfaro, A.; Tur, J. A.; Pons, A. (International Journal of Sports Medicine, 2012)
The aim was to study the effects of scuba diving immersion on plasma antioxidant defenses, nitric oxide production, endothelin-1 and vascular endothelial growth factor levels. 9 male divers performed an immersion at 50 m depth for a total time of 35 min. Blood samples were obtained before diving at rest, immediately after diving, and 3 h after the diving session. Leukocyte counts, plasma 8oxoHG, malondialdehyde and nitrite levels significantly increased after recovery. Activities of lactate dehydrogenase, creatine kinase, catalase and superoxide significantly increased immediately after diving and these activities remained high after recovery. Plasma myeloperoxidase activity and protein levels and extracellular superoxide dismutase protein levels increased after 3 h. Endothelin-1 concentration significantly decreased after diving and after recovery. Vascular endothelial growth factor concentration significantly increased after diving when compared to pre-diving values, returning to initial values after recovery. Scuba diving at great depth activated the plasma antioxidant system against the oxidative stress induced by elevated pO2 oxygen associated with hyperbaria. The decrease in endothelin-1 levels and the increase in nitric oxide synthesis could be factors that contribute to post-diving vasodilation. Diving increases vascular endothelial growth factor plasma levels which can contribute to the stimulation of tissue resistance to diving-derived oxidative damage.
Keywords: oxidative stress; antioxidant enzymes; hyperbaric oxygen; nitric oxide